Proceedings of the International Conference on Software and Systems Process 2016
DOI: 10.1145/2904354.2904373
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and improving effort estimation in Agile software development

Abstract: Effort estimation is more challenging in an agile context, as instead of exerting strict control over changes in requirements, dynamism is embraced. Current practice relies on expert judgment, where the accuracy of estimates is sensitive to the expertise of practitioners and prone to bias. In order to improve the effectiveness of the effort estimation process, the goal of this research is to investigate and understand the estimation process with respect to its accuracy in the context of agile software developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…However, expert estimates seem to be more accurate if domain knowledge is not included in the model or when uncertainty is high. The results also align with our previous case study in which we found that to improve expert‐based estimation, decision support is required that provides useful historical data and impact information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, expert estimates seem to be more accurate if domain knowledge is not included in the model or when uncertainty is high. The results also align with our previous case study in which we found that to improve expert‐based estimation, decision support is required that provides useful historical data and impact information.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have identified the need for considering the impact of a change on the underlying system to improve the effectiveness of expert‐based estimation methods. () Change impact analysis (IA) techniques identify software life cycle objects that are likely to be affected by a given change request …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanveer et al [12] performed an industrial case study to understand and improve e®ort estimation in ASD. The results showed that the accuracy of the e®ort estimation is a®ected by factors such as developers' knowledge and experience, and the complexity of the required changes in the system.…”
Section: 2mentioning
confidence: 99%
“…Performing a case study with a case company in the, we investigated why and how estimation is done and what factors are considered relevant for making estimates and for improving estimation accuracy. The study further established the need for tool support and helped to identify the requirements for such a tool.…”
Section: Introductionmentioning
confidence: 99%